The role of complement in the tick cellular immune defense against the entomopathogenic fungus Metarhizium robertsii - Fiorotti, Jéssica; Urbanová, Veronika; Gôlo, Patrícia Silva; Bittencourt, Vânia Rita Elias Pinheiro; Kopáček, Petr (Developmental and comparative immunology, 2022)
Entomopathogenic fungi (EPF) have been widely explored for their potential in the biological control of insect pests and as an environmentally friendly alternative to acaricides for limiting tick infestation in the field. The arthropod cuticle is the main barrier against fungal infection, however, an understanding of internal defense mechanisms after EPF intrusion into the invertebrate hemocoel is still rather limited. Using an infection model of the European Lyme borreliosis vector Ixodes ricinus with the EPF Metarhizium robertsii, we demonstrated that ticks are capable of protecting themselves to a certain extent against mild fungal infections. However, tick mortality dramatically increases when the capability of tick hemocytes to phagocytose fungal conidia is impaired. Using RNAi-mediated silencing of tick thioester-containing proteins (TEPs), followed by in vitro and/or in vivo phagocytic assays, we found that C3-like complement components and α2-macroglobulin pan-protease inhibitors secreted to the hemolymph play pivotal roles in M. robertsii phagocytosis.
Keywords: Entomopathogenic fungi; klíště; Lyme Disease; Biological control; Phagocytosis; zvířata; Thioester-containing proteins; Metarhizium; Ixodes; Tick; hemocyty; Hemocytes; lymeská nemoc; Animals